ANALISIS PENGARUH RAGAM MENU, PERSEPSI HARGA, LOKASI DAN KUALITAS LAYANAN TERHADAP MINAT BELI ULANG PADA SOTO SEDEEP BANYUMANIK CABANG AMBARAWA - Aufa, Zan Denniar; Kamal, Mustofa (Diponegoro Journal of Management, 2015)
Many new entrepreneurs, open a business in the culinary field. Soto Sedeep restaurant is one of them, the restaurant is located on Banyumanik which is a densely populated region and close to the campus. However, during the business, there are several constraints such as declining revenues in certain months. Researcher proposes the problem whether variety of menus, perception of price, location and quality of their services affect on consumer buying interest.In this study, researcher took 100 respondents. The sampling technique used in this research is non probability sampling. While the analysis tools using multiple regression technique.The result showed that the variety of menus variable is the most influential variable for consumer buying interest of 0.814, followed by the quality of service of -0.263, then the perception of the price of 0.253 and location of 0.071. From the four independent variables, quality service is the most negatively affect variable, while the other three are positively. And the location is the variable that does not significantly affect on buying interest. However from four independent variables, they jointly affect buying interest. The coefficient of determination in this study is 81.2%.